Meningkatkan motivasi belajar siswa pada pembelajaran IPS menggunakan model pembelajaran kooperatif tipe group investigation - Nur Laila; Hariyono Hariyono; Sumarmi Sumarmi (Jurnal Teori dan Praksis Pembelajaran IPS, 2016)
This study aims to increase students' motivation in learning Social Sciences through the implementation of cooperative learning model Group Investigation. The method used in this research is the Classroom Action Research are implemented in the first cycle and the second cycle. Each cycle consists of five convened four meetings in the classroom one meeting outside of instructional hours. The type of action taken is learning social studies using cooperative learning model type Group Investigation. Results of research conducted showed an increase in student motivation in the first cycle the percentage reached 77% criterion of "High" and the second cycle the percentage reached 96% criterion of "Very High". Happened percentage increase of 19%. Thus cooperative learning model of Group Investigation proven to increase students' motivation in learning social studies class VIII H SMPN 01 Batu City.Keywords: Group Investigation, motivation http://dx.doi.org/10.17977/um022v1i22016p123